Fluid-attenuated inversion recovery diffusion-weighted imaging (DWI) for evaluating chemotherapy response in patients with acute leukemia: Comparison with conventional DWI. - Tian, Xue; Niu, Jinliang; Li, Wenjin; Zhou, Xiaohong; Wu, Wenqi; Li, Xiaojun; Wang, Jun; Wang, Hongwei; Zhou, Xiaohong Joe (Indian Journal of Cancer)
Background: At present, the diagnosis and efficacy evaluation of acute leukemia (AL) are assessed by bone marrow aspiration, which is invasive and subject to sampling errors. Therefore, there is a pressing need to develop a noninvasive and accurate imaging method to evaluate bone marrow changes in patients with AL. This study aimed to compare the apparent diffusion coefficient (ADC) values obtained from fluid-attenuated inversion recovery diffusion-weighted imaging (FLAIR-DWI) and conventional DWI in the lumbar bone marrow of patients with AL and to investigate their performance for evaluating response to induction chemotherapy.Methods: A total of 28 patients with newly diagnosed AL and 25 patients with AL after induction chemotherapy underwent MRI scans at 1.5 Tesla using a conventional DWI and a FLAIR-DWI sequence on sagittal planes covering the lumbar bone marrow. Further, the ADC values from these two sequences, denoted as ADCCON and ADCFLAIR, were measured on multiple vertebrae. The percentage of leukemia cells in bone marrow was recorded, and bone marrow aspiration was performed on treated patients to determine complete remission (CR) and nonremission (NR).Results: ADCFLAIR [(0.453 ± 0.103) × 10-3 mm2/s] was significantly lower than ADCCON [(0.486 ± 0.096) × 10-3 mm2/s] in the 28 untreated patients (t = 3.051, P = 0.005). In the 25 treated patients, ADCFLAIR and ADCCON values [(0.566 ± 0.239) × 10-3 mm2/s] and [(0.716 ± 0.235) × 10-3 mm2/s], respectively, were higher compared with the untreated patients. The ADCCON values showed a nonsignificant difference between the CR (n = 18) and NR (n = 7) groups (t = 1.409, P = 0.305). However, the ADCFLAIR values exhibited statistically significant difference (t = 2.542, P = 0.018) between the two groups. In a receiver operator characteristic (ROC) analysis, the area under the curve (AUC) using ADCFLAIR (0.770) was larger than that of ADCCON (0.611) in distinguishing the CR and NR patients following the chemotherapy.Conclusion: Although both ADCCON and ADCFLAIR are sensitive to tissue changes induced by chemotherapy, FLAIR-DWI outperformed conventional DWI in separating AL patients with CR from NR after chemotherapy. A possible mechanism is that FLAIR-DWI suppresses signals from free water, making the ADC measurement more sensitive to structural changes in the bone marrow.